Beyond Borders: Migrants’ and Refugees’ Rights and Protection Under the Veil of International Law - Abdallah Mohamed Othman, El Nofely (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2021)
Migration has always been a phenomenal instrument throughout human survival and development. Since the dawn of history, people have been moving from one place to another seeking for better good welfare, employment opportunities, peace, or re-uniting with loved ones. This article argues that, despite the existence of regional and international instruments on the rights and principles governing the migration regime, yet, violations against migrants’ and refugees’ rights still persist. The study method used is literature with comparative approach. The results of the study, shows that the host states’ imposed discriminative legislation and a legal vacuum on punitive measures against violators of those principles contribute migration ordeal, and therefore, advocates for a strong regional and international coordination among the United Nations member states to develop long-term and viable solutions to enforce annulment of repressive migration laws, arbitrary detentions and forced deportations by the migrants-receiving states.